Association of HFE gene C282Y and H63D mutations with liver cirrhosis in the Lithuanian population - Simonas Juzėnas; Juozas Kupčinskas; Irena Valantienė; Jolanta Šumskienė; Vitalija Petrenkienė; Jūrate Kondrackienė; Laimutis Kučinskas; Gediminas Kiudelis; Jurgita Skiecevičienė; Limas Kupčinskas (Medicina, 2016)
Background and objective: Liver cirrhosis is the end-stage disease of chronic liver injury. Due to differences in the natural course of chronic liver diseases, identification of genetic factors that influence individual outcomes is warranted. HFE-linked hereditary hemochromatosis (HH) predisposes disease progression to cirrhosis; however, the role of heterozygous C282Y or H63D mutations in the development of cirrhosis in the presence of other etiological factors is still debated. The aim of this study was to determine the association between heterozygous C282Y and H63D mutations and non-HH liver cirrhosis in Lithuanian population. Materials and methods: The patient cohort consisted of 209 individuals. Diagnosis of cirrhosis was confirmed by clinical, laboratory parameters, liver biopsy, and radiological imaging. Control samples were obtained from 1005 randomly selected unrelated healthy individuals. HFE gene mutations were determined using the PCR-RFLP method. Results: The most common causes of cirrhosis were hepatitis C (33.9%), hepatitis B (13.6%), and alcohol (25.8%). C282Y allele was associated with the presence of cirrhosis (OR = 2.07; P = 0.005); this was also observed under recessive model for C282Y (OR = 2.06, P = 0.008). The prevalence of C282Y allele was higher in cirrhotic men than in controls (7.0% vs. 2.8%, P = 0.002). The carriage of H63D risk allele (OR = 1.54; P = 0.02), heterozygous C282Y/wt and homozygous H63D/H63D genotypes were associated with liver cirrhosis in males (OR = 2.48, P = 0.008, and OR = 4.13, P = 0.005, respectively). Conclusions: Heterozygous C282Y mutation of the HFE gene was associated with liver cirrhosis in the Lithuanian population. In gender-related analysis, heterozygous C282Y and homozygous H63D mutations were linked to liver cirrhosis in men, not in women.